Optimization of Mechanical Crimping in the Terminal Crimping Process Using a Response Surface Methodology - Kaona Jongwuttanaruk; Chalermsak Thavornwat (Advances in Materials Science and Engineering)
This research aims to optimize the tensile mechanical properties in the terminal crimping process in the terminal 064 series using central composite designs (CCD) of response surface methodology (RSM) on pull force using the Minitab 18 Program. Pull force testing is the mechanical property of the indicator in the crimping process. Three independent variables of the crimp dimensions were studied, including crimp height, crimp depth, and crimp width. The optimum crimp dimensions to sustain a maximum impact pull force of 13.60 Kgf were a crimp height of 1.25 mm, crimp depth of 2.36 mm, and crimp width of 1.48 mm for a compaction ratio of 18.63%. The tolerance on the crimp height of 0.05 mm maintained the compaction ratio within the SAE/USCAR-21 Revision 4 standard compaction range of 15 to 20%. This specification requires three consecutive crimp heights to pass electrical and mechanical tests. Using samples built to this compaction range provides the best opportunity to pass such tests whilst also addressing the problem of loose wire strands for a pull force of more than 8 Kgf. Finally, an optimization analysis is carried out to select the finest conditions for the process.